Description of final stadium larva of Erythrodiplax connata and E. basifusca and redescription of that of E. minuscula (Odonata: Libellulidae) - Lozano, Federico (2011)
In this contribution the final stadium larvae of Erythrodiplax connata and E. basifusca are described and that of E. minuscula is redescribed. Diagnoses are provided for the larvae of the genus Erythrodiplax and for those included in the connata group. E. connata lacks lateral spines on abdominal segments, a character which has not been observed in any other larvae of the genus. Finally, due to the fact that the larvae of E. connata could not be reared successfully until emergence, differences with other sympatric Patagonic Libellulidae are discussed.